Etika komunikasi Islam mahasiswa organisasi PMII (Pergerakan Mahasiswa Islam Indonesia) dalam menangkal berita hoaks di Facebook - Ila Khafia Wafda (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2020)
This study aims to see how Islamic communication ethics is in an effort to ward off hoax news on Facebook that hit students of the PMII. The reason is, the existence of hoax reporting on Facebook contradicts the vision of the PMII organization which is committed to being a forum for strengthening aqidah, morals, and creating a society like the Ummah. The research used qualitative research methods through in-depth interview approaches and observations of active students in the PMII organization uses a sampling technique based on purposive sampling technique. The results showed that students instilled communication ethics according to Islamic law in using Facebook social media, so steps need to be taken to communicate in accordance with Islamic teachings to avoid the rampant hoax news on Facebook to promote morals according to Islamic law refer to the example of the Prophet, p.b.u.h. That it is important for PMII student organizations to promote morals in accordance with Islamic law, and also apply communication ethics in accordance with Islamic law by promoting the principles of Islamic communication, namely: qawlan sadidan, qawlan balighan, qawlan maysura, qawlan layyina, qawlan karima, qawlan ma'rufa. So it is necessary to understand and apply Islamic communication ethics by students of the PMII organization so that it becomes the basis for accessing Facebook.